Molecular investigation on hazelnut-associated Fusarium isolates belonging to the Fusarium citricola species complex - Brugneti, Federico; Turco, Silvia; Ukwibishaka, Nepomuscene; Abramczyk, Barbara; Cardacino, Antonella; Mazzaglia, Angelo; Nicoletti, Rosario; De Masi, Luigi; Zimowska, Beata (Frontiers in Microbiology, 2026)
Recent studies on Fusaria associated with hazelnut have pointed out a role of these fungi as both disease agents and endophytic symbionts, raising concern for the possible mycotoxin contamination of kernels and derived products. Molecular evidence has shown that previous classifications of these isolates as Fusarium lateritium were incorrect, indicating that most of them instead belong to the Fusarium citricola species complex (FCCSC). Based on a set of isolates collected in Italy and Poland, the present work provides a phylogenetic analysis supported by three species delimitation algorithms. The results confirm that all the available hazelnut isolates belong to the FCCSC, and that the discrimination between three currently accepted taxa in this species complex, namely F. aconidiale, F. celtidicola and F. juglandicola, should be reconsidered. The inclusion in our analysis of 25 species identified in the closely related Fusarium tricinctum species complex provides an indication that the statistical methods for species delimitation represent a useful tool for checking the reliability of the species boundaries currently defined in these fungi.